(untitled) (Olhar de Professor, 2025)
There are many possible theoretical, methodological and procedural approaches to analyzing documents with unique characteristics, such as the materials from the United Nations Educational, Scientific and Cultural Organization (UNESCO) and the United Nations Development Program (UNDP) analyzed in this study. These are extensive textual productions that address a variety of issues when they are intended to speak to States, governments and civil society organizations. This article adopted a particular approach by analyzing diagnoses of the challenges faced in the Latin American continent in the field of education, as well as guidelines related to possible ways to overcome the failure to respect children’s human rights. There is a substantial gap between the few advances detected and the prescriptive proposals that aim to guarantee boys and girls of all groups and social classes the right to learning opportunities. In the prescriptive proposals (more than in the diagnoses listed in this report) the ambiguity and ambivalences are potentially evident.